2012
DOI: 10.1002/pi.4214
|View full text |Cite
|
Sign up to set email alerts
|

On the phase behaviour of organic semiconductors

Abstract: The physical organisation, from the molecular to the macroscale, of functional organic matter such as polymer semiconductors can profoundly affect the properties and features of the resulting architectures and their consequent performance when used as active layers in organic optoelectronic devices, including organic thin-film field-effect transistors, organic light-emitting diodes or organic photovoltaic cells. Here, we present a survey on the principles of structure development from the liquid phase of this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
41
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(41 citation statements)
references
References 39 publications
0
41
0
Order By: Relevance
“…Both, the optoelectronic properties and the structural aspects of these systems have to be optimized to reach good performance in the final applications. The structures formed can be controlled by rational design or by applying different processing techniques . Supramolecular chemistry is an alternative to achieve such control, especially when using small molecules.…”
Section: Methodsmentioning
confidence: 99%
“…Both, the optoelectronic properties and the structural aspects of these systems have to be optimized to reach good performance in the final applications. The structures formed can be controlled by rational design or by applying different processing techniques . Supramolecular chemistry is an alternative to achieve such control, especially when using small molecules.…”
Section: Methodsmentioning
confidence: 99%
“…Several studies have already indicated that P3HT/PC 61 BM exhibits eutectic phase behaviour, apparent through the melting point depression of the two components when mixed . At the eutectic composition, both components solidify or desolidify simultaneously.…”
Section: Introductionmentioning
confidence: 99%
“…This yields a fine grain morphology upon cooling which, although not a one‐phase system, will desolidify upon heating at a single temperature and form again a mixed phase of eutectic composition. It is known that P3HT and PC 61 BM are miscible in the amorphous phase, while leading to separate P3HT or PC 61 BM crystals . Different P3HT/PC 61 BM ratios are described in the literature for the eutectic composition, depending on the methodology and the P3HT used .…”
Section: Introductionmentioning
confidence: 99%
“…One key factor is the molecular weight of the polymer. Variations in molecular weight can directly affect the solid‐state structure of polymers such as the prototypical poly(3‐hexylthiophene) (P3HT) . At very low molecular weights P3HT forms a one‐phase, paraffinic structure comprised of unconnected, chain‐extended crystallites.…”
Section: Introductionmentioning
confidence: 99%